Intelegensi Quotient Pada Anak Usia Prasekolah Ditinjau Dari Stimulasi Pendidikan Anak Usia Dini - Intan Fazrin; Heri Saputro; Arina Chusnatayaini (STRADA : Jurnal Ilmiah Kesehatan, 2017)
The child is a unique creature, the family expects that the child will grow optimally, the factors that influence the optimal growth and development of the most dominant after pasalkanatal are genetic, environment and family. The purpose of this study is to know the relationship between intelligence quotient with educational stimulation in early childhood. The research design used was correlational with cross sectional approach. The population studied by all families who have preschool children in kindergarten Dharma Wanita Banaran Kediri, with propotional stratified random sampling technique obtained sample amounted to 53 respondents. Data collection using questionnaire, the results were analyzed using spearman test at α = 0,05. The results of the study most of respondents assessed the educational stimulation of children aged within the category enough, ie 28 respondents (52.8%). Nearly the average upper quotient intelligence with 30 respondents (55.6%) The results of the analysis (p = 0,000) indicate that there is an association of early childhood educational stimulation with quotient intelligence in preschoolers. Needs intelligence quotient of stimulation is needed for the child's intellectual development process. The role of the family is to provide facilities for children to facilitate children to go to school in educational facilities that have good quality and provide stimulation independently when the child at home